Systematic Literature Review: Online Learning during Covid-19 Pandemic - Nugroho Nugroho (Institut Agama Islam Negeri Palopo, 2022)
This research was conducted in the odd semester of 2021-2022. The approach used is a systematic literature review. This study followed the seven stages of Petticrew and Roberts’s systematic review: defining the research question or hypothesis, determining the type of study, conducting a comprehensive literature search, filtering the search results, assessing the included studies, and synthesizing the studies. and assessing heterogeneity among studies(Petticrew & Roberts, 2006). The researcher used Publish or Perish and Atlas.ti 8 to help this study. This study aims to determine the form and effectiveness of the influence of online learning during the Covid-19 pandemic. The results of the study found that there were psychological and physical effects and learning outcomes of students during online learning. This study also found several strategies used during online learning. This study suggests that the government through universities should provide adequate infrastructure for lecturers and students to organize online learning during Covid-19. Standards for organizing and training for lecturers to organize online learning should be carried out as soon as possible. Counseling guidance for students who have problems needs to be prepared by both the government and universities.